Evaluating Player Experience for Fear Modeling of 2D East Java Horror Game Alas Tilas - Harits Ar Rosyid; Aji Prasetya Wibawa; Esther Irawati Setiawan; Herman Thuan To Saurik (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2023)
Developing a 2D horror game and evaluating the reliability of the player experience are two things that are interrelated and equally important. Developers must ensure that the game can provide a satisfying and reliable gaming experience for their players. This study aims to evaluate the reliability of the player's experience in the game entitled Alas Tilas, East Java. This study used the User Experience Questionnaire (UEQ) in Indonesian as a survey approach method, which was given to 30 teenagers who at least played horror games once. UEQ may provide feedback to developers on the attractiveness, clarity, efficiency, accuracy, stimulation, and novelty aspects of the game. From the results of the UEQ, a reliability test will be carried out using the Cronbach Alpha technique. The results of the descriptive analysis show that these variables are Attractiveness (mean, 0.933), Clarity (mean, 1.808), Efficiency (mean, 1.508), Accuracy (mean, 0.217), Stimulation (mean, 0.667) and Novelty (mean, 0.242). Attractiveness, clarity, and efficiency averaged positive results. The average aspects of accuracy, stimulation, and novelty of the game get neutral results. The results of the reliability test conducted on UEQ data obtained a Cronbach alpha value > 0.6 which indicates that the research data used to test the player experience are considered reliable so that they can be used to provide input for future development of the Alas Tilas game. To increase the average score, the researcher provides recommendations for improvement, namely, adjusting the accuracy and novelty aspects of the horror scenario game entitled Alas Tilas East Java. Therefore, it is expected to improve the quality of the game.